Kode Etik Public Relation Perhumas dan APRI di Indonesia - Siregar, M Hafiz; Sakinah, Nurul; Salisah, Fadiah Anggi; Amri, Khairul; Kurniawan, Ade (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Exploring the Code of Ethics in the Public Relations (PR) profession marks an important milestone in modern communication practice. This article explores the Code of Ethics adopted by the Indonesian Public Relations Association (Perhumas) and the Indonesian Public Relations Association (APRI) in Indonesia. Through a scientific approach, this article presents in-depth analysis of the significance, scope, and implementation of the Code of Ethics in the context of PR. The discussion covers normative, ethical, and moral responsibilities inherent in the role of PR practitioners in society. A deep understanding of this Code of Ethics serves as the main foundation in creating a positive image for PR professionals and the organizations they represent. This article also emphasizes the importance of understanding the role of law in communication activities, illustrating the integral relationship between ethical principles and legal foundations in effective and responsible PR practice.